Strain hardening fiber reinforced cement composites for the flexural strengthening of masonry elements of ancient structures - Esmaeeli, Esmaeel (2013)
To assess the strengthening ability of a strain hardening cementitious composite (SHCC), a layer of SHCC was applied to masonry beams subjected to bending. When compared to the strengthening performance of steel fibre reinforced self-compacting concrete (SFRSCC) layer for this type of brittle beams, the SHCC presented better workability in fresh state, and provided a higher load carrying capacity and deflection ductility even with a smaller layer thickness. By using the data derived from the experimental tests with the constituent materials of the strengthened masonry beams, the behaviour of the tested strengthened masonry beams was numerically simulated with good accuracy.